Pembekalan Kemampuan Menulis Ilmiah Bagi Siswa Sekolah Menengah di Lombok Timur - Herayanti, Lovy; Sukroyanti, Baiq Azmi; Gunawan, Gunawan; Nisrina, Nina (Indonesian Publication Center, 2023)
This article discusses the implementation of a training program aimed at enhancing scientific writing skills for high school students in East Lombok. The background reflects the need for strong scientific writing skills in the face of current educational challenges. The main objective of this program is to improve students' abilities to compose and present high-quality scientific writings. The methods employed include a series of intensive training sessions, workshops, and focus group discussions. Conducted in East Lombok, the program was designed to address the specific needs of students in that region. In conclusion, the initiative has successfully provided a profound understanding of scientific writing to the students, boosting their confidence and fostering an interest in scientific literacy. The utilization of intensive training, workshops, and focus group discussions has proven effective in achieving the objectives of the program.